Sweet waste medieval sugar production in the Mediterranean view from the 2002 excavation at Tawahin es-Sukkar, Safi, Jordan - Jones, R. E. 20./21. Jh (Potingair, 2017)
"The history of cane sugar from its origins in the east to its status as a luxury foodstuff and even medicine in the medieval period to a commodity produced and consumed globally in today's world is well known. Yet archaeologically, sugar is an invisible commodity, its presence usually being inferred from the humble sugar pots used in the last stages of its sophisticated production process. Despite its considerable importance as a food stuff in medieval Near East and Europe, sugar has received much less archaeological attention than has been devoted to oil and wine. This book attempts to redress the imbalance between history and archaeology by reporting on the excavation of a medieval sugar refinery, Tawahin es-Sukkar near Safi, situated south of the Dead Sea in Jordan. There it was possible to explore many of the steps in the process from milling/crushing of the cane to the purifying of the crude juice. The book's title refers to the industrial waste whose study has shed light on those steps. To place this refinery in chronological and economic context, excavation was extended to the adjacent 'support town' of Khirbet Shaykh 'Isa. The available archaeological evidence for production across the Mediterranean up to the time that the industry's focus moved increasingly west to the New World is reviewed. There is particular emphasis on the sugar vessels and the light they can shed on the poorly understood relationship between primary production centres, refining, storage and consumption centres. the book, which is fully illustrated, can be profitably read by archaeologists, archaeological scientists, historians and vistors to Jordan alike"--Back cover
Keywords: Geschichte 1000-1500; Geschichte; Ausgrabung; Zuckerproduktion; Jordanien; Sugarcane industry / Jordan / History; Sugarcane industry / Mediterranean Region / History; Excavations (Archaeology) / Jordan; Excavations (Archaeology); Sugarcane industry; Jordan; Mediterranean Region; History